2014
DOI: 10.1007/s12195-014-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Senescence Increases Traction Forces due to Age-Associated Changes in the Glycocalyx and SIRT1

Abstract: Endothelial cell (EC) aging and senescence are key events in atherogenesis and cardiovascular disease development. Age-associated changes in the local mechanical environment of blood vessels have also been linked to atherosclerosis. However, the extent to which cell senescence affects mechanical forces generated by the cell is unclear. In this study, we sought to determine whether EC senescence increases traction forces through age-associated changes in the glycocalyx and antioxidant regulator deacetylase Sirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Ageing occurs as a result of cellular senescence, and the occurrence and development of age-related cardiovascular diseases are associated with the senescence of vascular cells (Cheung et al, 2015). Cell senescence is a complex pathophysiological process, which involves multiple factors regulated by the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Ageing occurs as a result of cellular senescence, and the occurrence and development of age-related cardiovascular diseases are associated with the senescence of vascular cells (Cheung et al, 2015). Cell senescence is a complex pathophysiological process, which involves multiple factors regulated by the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…During senescence the glycocalyx of vascular endothelium and erythrocytes is gradually compromised [45, 46]. In dialysis patients this process is supposedly accelerated.…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous actin (F-actin) is critical for stress responses and also mediates ECM nuclear–mechanical coupling [ 37 ]. Cheung et al investigated whether the senescence of human endothelial cells (ECs) is associated with an increase in traction forces through modification in the antioxidant regulator deacetylase Sirtuin1 (SIRT-1), commonly downregulated during aging [ 38 ]. The authors found that traction forces were higher in aged ECs, and this increase correlated with abnormal actin localization.…”
Section: Mechanical Changes In Aging Cytoskeletonmentioning
confidence: 99%